Increasing temperature within thermal limits compensates negative ultraviolet‐B radiation effects in terrestrial and aquatic organisms. Issue 11 (24th July 2019) - Jin, Peng; Overmans, Sebastian; Duarte, Carlos M.; Agustí, Susana
Abstract: Aim: The interactive effects of increased temperature and ultraviolet‐B (UV‐B) radiation on terrestrial and aquatic biota remain poorly understood. Our goal is to increase knowledge by providing a comprehensive assessment of the combined effects of warming and increased UV‐B on organisms across these domains. Location: Global. Time period: 1995–2016. Major taxa studied: Terrestrial plants and animals, and marine and freshwater microalgae, macroalgae and animals. Methods: We examined, using a meta‐analysis based on 1, 139 published experimental assessments, the combined effects of temperature and UV‐B across terrestrial, freshwater and marine biota. We characterized the prevailing mode of combined effects (additive, synergistic or antagonistic), and assessed whether these were dose‐dependent or differed between terrestrial, freshwater and marine species, or between organisms growing in the Northern and Southern Hemispheres. Results: Our results show that the two stressors generally acted opposingly, with a significant positive effect of increased temperature and a significant adverse effect of elevated UV‐B radiation. Regarding their interactive impact, additive interactions (84%) appeared to be much more common compared with multiplicative (16%) effects. The frequencies of interaction types differed significantly among the three habitats and different plant functional groups. The proportion of both synergistic and antagonistic effects increased with increasing magnitude of temperature and UV‐B changes, suggesting that additivity is constrained by an organism's thermal and physiological limits. Main conclusions: Our analysis demonstrates that due to their mostly opposing nature, elevated temperature, within the thermal limits of organisms, tends to compensate for the negative impact of UV‐B radiation when acting together, while their additive interaction is likely to assist impact prognosis. Our study, therefore, provides new insights into the predictions of the interactive effects of global change drivers across different habitats.